Copper-Catalyzed N-Arylation of Sulfoximines with Arylboronic Acids under Mild Conditions - Gupta, Surabhi; Baranwal, Siddharth; Muniyappan, Nalluchamy; Sabiah, Shahulhameed; Kandasamy, Jeyakumar (Synthesis, 2019)
N-Arylation of sulfoximines with different arylboronic acids, including sterically hindered boronic acids, is achieved using copper(I) iodide and 4-DMAP at room temperature. Moreover, N-arylation of biologically relevant l-methionine sulfoximine is demonstrated for the first time. All these reactions provided the desired products in excellent yields within a short span of time. The optimized reaction conditions are well suited to the task of N-vinylation of sulfoximine with trans-2-phenylvinylboronic acid.
Keywords: arylation; boronic acid; sulfoximine; catalysis; copper